An organic calcium-phosphorus compound from rice polishings and its manufacture into pharmaceutical tablets - Vachananda, Phison 1933-
An organic compound containing calcium and phosphorus was isolated from four batches of rice polishings obtained from various rice-producing localities in the Philippines, by extraction with dilute hydrochloric acid and precipitation with dilute ammonium hydroxide. An average yield of 12.82% of this compound was obtained from the samples of rice brans. Upon analysis, the isolated compound was found to contain an average of 2.57% calcium, 0.72 % phosphorus, 68.18% carbon, 19.56% hydrogen and 1.29% nitrogen. An attempt has been made to establish the empirical formula of the isolated compound but the percentages of carbon, hydrogen, nitrogen and oxygen obtained are inconsistent. However, the contents of calcium and phosphorus are fairly constant. It is therefore recommended that further work on its complete chemical identification be undertaken in the future. Using this calcium-phosphorus compound, three different formulations were processed into tablets. Starch powder was used as the disintegrator, starch paste 1:10 and plasdone solutions were tried as binders and magnesium stearate either alone or in combination with starch powder was employed as the lubricant. The finished tablets were then tested for hardness, disintegration and weight variation in accordance with the official procedures given in the U.S.P. XVI, and the results, tabulated. Tablets prepared according to Formulation III showed satisfactory hardness, rapid disintegration time, and weight variations which are within the limits set by the U.S.P. XVI. No difficulties were encountered in the granulation of the materials as well as in the compression of the tablets. A bigger batch size of Formulation III was processed to determine its reproducibility in large-scale production. This was indicated as Formulation IIIa.